Expression of Nuclear Factor Erythroid 2 Protein in Malignant Cutaneous Tumors - Choi, Chang Yong; Kim, Jin Young; Wee, Seo Yeong; Lee, Jang Hyun; Nam, Doo Hyun; Kim, Chul Han; Cho, Moon Kyun; Lee, Yoon Jin; Nam, Hae Seon; Lee, Sang Han; Cho, Sung Woo (Archives of Plastic Surgery, 2014)
Background Reactive oxygen species (ROS) damages cell molecules, and modifies cell signaling. The nuclear factor E2-related factor (Nrf2) is a critical transcription regulator, which protects cells against oxidative damage. Nrf2 expression is increased in a large number of cancers. However, little information has been reported regarding the expression of Nrf2 in skin cancers. Hence, we explored the expression of Nrf2 protein in skin cancers.Methods The Nrf2 protein expression in 24 specimens, including 6 malignant melanomas (MM), 6 squamous cell carcinomas (SCC), 6 basal cell carcinomas (BCC), and 6 normal skin tissues, was evaluated by western blotting. Immunohistochemical staining was performed. The expression of Kelch-like ECH-associated protein 1 (Keap1), the key regulator of Nrf2, was also analyzed by western blotting.Results Small interfering RNA transfection to the melanoma cell line G361 confirmed that an approximately 66 kDa band was the true Nrf2 band. The western blot revealed that the Nrf2 protein was definitely expressed in normal skin tissues, but the Nrf2 expression was decreased in MM, SCC, and BCC. Immunohistochemical examination showed that expression of Nrf2 was decreased in all skin cancer tissues compared to the normal skin tissues. Keap1 was not expressed in all malignant skin tumors and normal skin tissues by western blot.Conclusions ROS was increased in various types of cancers which proteins were highly expressed or underexpressed. This study demonstrated that the expression of Nrf2 protein was down-regulated in human malignant skin tumors. We suggest that decreased expression of Nrf2 is related to skin cancers.
Keywords: NF-E2-related factor 2; Reactive oxygen species; Skin neoplasms